RecA4142 Causes SOS Constitutive Expression by Loading onto Reversed Replication Forks in Escherichia coli K-12 - Long, Jarukit Edward (American Society for Microbiology (ASM), 2010)
Escherichia coli initiates the SOS response when single-stranded DNA (ssDNA) produced by DNA damage is bound by RecA and forms a RecA-DNA filament. recA SOS constitutive [recA(Con)] mutants induce the SOS response in the absence of DNA damage. It has been proposed that recA(Con) mutants bind to ssDNA at replication forks, although the specific mechanism is unknown. Previously, it had been shown that recA4142(F217Y), a novel recA(Con) mutant, was dependent on RecBCD for its high SOS constitutive [SOS(Con)] expression. This was presumably because RecA4142 was loaded at a double-strand end (DSE) of DNA. Herein, it is shown that recA4142 SOS(Con) expression is additionally dependent on ruvAB (replication fork reversal [RFR] activity only) and recJ (5′→3′ exonuclease), xonA (3′→5′ exonuclease) and partially dependent on recQ (helicase). Lastly, sbcCD mutations (Mre11/Rad50 homolog) in recA4142 strains caused full SOS(Con) expression in an ruvAB-, recBCD-, recJ-, and xonA-independent manner. It is hypothesized that RuvAB catalyzes RFR, RecJ and XonA blunt the DSE (created by the RFR), and then RecBCD loads RecA4142 onto this end to produce SOS(Con) expression. In sbcCD mutants, RecA4142 can bind other DNA substrates by itself that are normally degraded by the SbcCD nuclease.